A Collocation Method for Numerical Solution of Hyperbolic Telegraph Equation with Neumann Boundary Conditions. (28th September 2014) - Mittal, R. C.; Bhatia, Rachna
Abstract : We present a technique based on collocation of cubic B -spline basis functions to solve second order one-dimensional hyperbolic telegraph equation with Neumann boundary conditions. The use of cubic B -spline basis functions for spatial variable and its derivatives reduces the problem into system of first order ordinary differential equations. The resulting system subsequently has been solved by SSP-RK54 scheme. The accuracy of the proposed approach has been confirmed with numerical experiments, which shows that the results obtained are acceptable and in good agreement with the exact solution.